Swedish Equity Mutual Funds 1993-2013: Performance, Persistence and Presence of Skill - Harry Flam; Roine Vestman (Center for Economic Studies and ifo Institute (CESifo), 2017)
Actively managed Swedish equity mutual funds outperform the market in 1993-2001 but have negative gross and net excess returns of -0.18 and -1.47 per cent per year in 2002-2013. Across funds, there is no correlation between activism and return in the later period. Returns show little or no persistence: When funds are ranked on past performance, their returns converge to the cross-sectional mean in about two years and stay close to that subsequently. There is practically no evidence of stock-picking skills: Actual gross excess returns do not differ significantly from bootstrapped excess returns under the hypothesis of no skill in the population.
Keywords: G23; 330; mutual funds; index funds; fund performance; fund return persistence; management skill; luck